Etiology of recurrent large vessel occlusions treated with repeated thrombectomy. Issue 2 (April 2020) - Ikenberg, B; Rösler, J; Seifert, CL; Wunderlich, S; Kaesmacher, J; Zimmer, C; Boeckh-Behrens, T; Friedrich, B; Maegerlein, C
Background: Repeated mechanical thrombectomy for acute stroke treatment in individual patients has been proven feasible. However, less is known about the etiology of recurrent vessel occlusions after prior thrombectomy. We aimed to understand if the etiology of such recurrent events differs from the first stroke. Methods: Retrospectively, we identified all patients at our center who received a repeated mechanical thrombectomy between 2007 and 2019. Clinical data were retrieved from medical records. Etiology of stroke was evaluated retrospectively, and angiographic studies were revisited. Results: Twenty-three patients (1.5%) were identified. Median age was 68 years (IQR 56–77). Median NIHSS at first admission was 11 points (IQR 5–15). In nine cases (39.1%), the recurrent vessel occlusion was located exactly at the same position as the prior occlusion. Overall, five (21.7%) patients had a remarkable extracranial pathology as likely cause of stroke recurrence. In 16 patients (69.6%), the etiology of the first stroke and its recurrence was considered as likely being the same, mostly of cardioembolic or unknown origin. In the seven remaining patients (30.4%), the cause of stroke possibly differed from the first event, with five patients (21.7%) having a postinterventional intracranial intimal lesion as possible cause of stroke. Conclusion: Incidence of repeated thrombectomy was low. However, the high number of patients with known origin of stroke etiology raises the question how their monitoring may be optimized. The number of patients with remarkable extracranial pathologies or intracranial endothelial lesions supports current clinical practice to pay attention to final angiographic series.